Scenarios for European agricultural policymaking in the era of digitalisation. (February 2022) - Ehlers, Melf-Hinrich; Finger, Robert; El Benni, Nadja; Gocht, Alexander; Sørensen, Claus Aage Grøn; Gusset, Markus; Pfeifer, Catherine; Poppe, Krijn; Regan, Áine; Rose, David Christian; Wolfert, Sjaak; Huber, Robert
Abstract: CONTEXT: Digitalisation affects the agri-food sector and its governance. However, what digitalisation of the sector will imply for future agricultural policymaking remains unclear. OBJECTIVE: The objective of the study is to develop and evaluate explorative scenarios of digitalisation in the agri-food sector of Europe that are explicitly relevant to agricultural policy. The study aims to provide guidance for strategic development of agricultural policy to address the potentials, uncertainties and unknowns arising with digitalisation of the sector. METHODS: We combine a Delphi study and a participatory scenario workshop to develop and evaluate plausible explorative scenarios of digitalisation of Europe's agri-food sector. For all scenarios we identify gaps in achieving a range of important European agricultural policy goals, drawing on the Delphi study and desk-based analysis. Subsequently we deduce strategies to address these agricultural policy gaps. RESULTS AND CONCLUSIONS: Four scenarios of digitalisation of the agri-food sector were developed for Europe in 2030. They comprise of 1) digitalisation of the sector following current directions at current rates as a baseline scenario, 2) strong digitalisation of a regulatory government, 3) use of autonomous farming technology and 4) digitalised food business. These explorative scenarios entail various gaps in achieving European agricultural policy goals. Our findings suggest that the baseline scenario needs strategies to ramp up technological and institutional infrastructure for digitalisation. The other scenarios need strategies to prevent risks, e.g., of technological failures or undesired social impacts. They also need strategies to cater for special cases and diversity, e.g., of ecosystems and farming practices. Across the scenarios, it seems useful to increase digital competencies of the stakeholders. SIGNIFICANCE: The study is the first that derives implications for policy strategies from explorative scenarios of future digitalisation of agricultural systems that target gaps in achieving agricultural policy goals. The combination of developing and analysing scenarios generated findings that are of significance to policymaking stakeholders and researchers alike, who all need to address the uncertainties arising with future digitalisation of the agri-food sector. Graphical abstract: Unlabelled Image Highlights: The future for agricultural policy is uncertain, as digitalisation of the sector progresses. We develop scenarios of digitalisation of Europe's agri-food sector and derive strategies to address their policy gaps. We combine a Delphi study and participatory workshop to develop scenarios. Strategies that increase digital competencies, prevent risks and cater for diversity could address policy gaps in 2030. This is the first study to derive strategies addressing policy gaps arising in scenarios of agricultural digitalisation.